Tensões e conexões: um estudo sobre multinacionais e sistemas nacionais de inovação - Leandro Alves Silva (2014)
Multinational companies have historically placed the national innovation systems (NSI) under strain. To understand that strain is necessary to understand the nature of the multinational corporation and its role within the national innovation system. In turn, from national innovation system is expected more conceptual accuracy in order to multinational firm (while one of its elements) and the structure of system can be applied to the understanding of this tension. This thesis is an attempt to combine the analysis of multinational enterprise and analysis of national innovation systems, in order to understanding the mutual influence they exert each other. In general, the multinational company appears as dependent on context, either in its emergence (origin) or in its operations (destination), while the national innovation system is taken as the environment (context) of the multinational in the origin and destination. Thus, the NSI is assumed as a source of ownership advantages for multinational firms and as a locational advantage of countries. The central results of this thesis are that 1) the tension generated by the multinational company on the national innovation system becomes endogenous, to the extent that 2) the multinational company emerges from a particular NSI and operates in multiple national innovation systems, which it connects inside and outside its hierarchy.